A child with Chronic Nonbacterial Osteomyelitis and celiac disease: accidental association or two different aspects of the same condition? - Grazia Bossi; Maria Sole Prevedoni Gorone; Luca Lungarotti; Francesco Pelillo; Amelia Mascolo; Matteo Naso; Daniele Veraldi; Francesca Olivero; Costanza Chirico; Maria Vittoria Marino; Cristina Dutto; Gian Luigi Marseglia (Italian Journal of Pediatrics)
Abstract Background Chronic Nonbacterial Osteomyelitis (CNO) is a rare auto-inflammatory disease that mainly affects children, and manifests with single or multiple painful bone lesions. Due to the lack of specific laboratory markers, CNO diagnosis is a matter of exclusion from different conditions, first and foremost bacterial osteomyelitis and malignancies. Whole Body Magnetic Resonance (WBMR) and bone biopsy are the gold standard for the diagnosis. Although the association with Inflammatory Bowel Disease (IBD) has been reported in the literature, cases of CNO in celiac patients have never been described before. Case presentation We report about a girl of 3 years and 8 months of age who presented with severe bone pain, slight increase of inflammatory markers, micro-hematuria and high calprotectin values. Her personal medical history was uneventful, apart from low weight growth. She had never complained of abdominal pain or other gastro-intestinal symptoms. WBMR showed the classical features of multifocal CNO, and biopsy confirmed the diagnosis. Celiac disease (CD) was suspected on the basis of antibody screening, and confirmed by gut biopsy. With gluten-free diet the patient achieved rapid and complete symptom remission together with healing of all the bone lesions proven by WBMR. Three years after the onset of the disease the girl is healthy and totally asymptomatic, still on clinical and radiological follow-up. Conclusions Based on our experience, the diagnostic work-up of new cases of CNO should include the screening test for CD and, according to the literature, the possibility of IBD should also be properly ruled out. When CNO and CD coexist, gluten-free diet, combined with antinflammatory therapy, could be able to completely reverse bone lesions, shortening the duration of medical treatment. Because the diseases’ onset is seldom simultaneous, patients with CNO and IBD deserve a properly extended follow-up. Finally, the analysis of the relationship between CNO and autoimmune intestinal diseases provides a unique opportunity to understand the pathophysiological pro-inflammatory network underlying both types of disorders and it is necessary to make the most suitable therapeutic choice.